Analysis of optical solitons solutions of two nonlinear models using analytical technique - Ullah, Naeem; Asjad, Muhammad Imran; Azhar Iqbal; Rehman, Hamood Ur; Hassan, Ahmad; Gia, Tuan Nguyen (AIMS mathematics, 2021)
Looking for the exact solutions in the form of optical solitons of nonlinear partial differential equations has become very famous to analyze the core structures of physical phenomena. In this paper, we have constructed some various type of optical solitons solutions for the Kaup-Newell equation (KNE) and Biswas-Arshad equation (BAE) via the generalized Kudryashov method (GKM). The conquered solutions help to understand the dynamic behavior of different physical phenomena. These solutions are specific, novel, correct and may be beneficial for edifying precise nonlinear physical phenomena in nonlinear dynamical schemes. Graphical recreations for some of the acquired solutions are offered.